Urban legends series: oral manifestations of HIV infection. (21st March 2013) - Patton, LL; Ramirez‐Amador, V; Anaya‐Saavedra, G; Nittayananta, W; Carrozzo, M; Ranganathan, K
<x xml:space="preserve">Abstract</x> Human immunodeficiency virus‐related oral lesions (HIV‐OLs), such as oral candidiasis (OC) and oral hairy leukoplakia (OHL), have been recognized as indicators of immune suppression since the beginning of the global HIV epidemic. The diagnosis and management of HIV disease and spectrum of opportunistic infection has changed over the past 30 years as our understanding of the infection has evolved. We investigated the following controversial topics: (i) Are oral manifestations of HIV still relevant after the introduction of highly active antiretroviral therapy (HAART)? (ii) Can we nowadays still diagnose HIV infection through oral lesions? (iii) Is the actual classification of oral manifestations of HIV adequate or does it need to be reviewed and updated? (iv) Is there any novelty in the treatment of oral manifestations of HIV infection? Results from extensive literature review suggested the following: (i) While HAART has resulted in significant reductions in HIV‐OLs, many are still seen in patients with HIV infection, with OC remaining the most common lesion. While the relationship between oral warts and the immune reconstitution inflammatory syndrome is less clear, the malignant potential of oral human papillomavirus infection is gaining increasing attention. (ii) Effective antiretroviral therapy has transformed HIV from a fatal illness to a chronic manageable condition and as a result expanded screening policies for HIV are being advocated both in developed and in developing countries. Affordable, reliable, and easy‐to‐use diagnostic techniques have been recently introduced likely restricting the importance of HIV‐OLs in diagnosis. (iii) The 1993 EC‐Clearinghouse classification of HIV‐OLs is still globally used despite controversy on the relevance of periodontal diseases today. HIV‐OL case definitions were updated in 2009 to facilitate the accuracy of HIV‐OL diagnoses by non‐dental healthcare workers in large‐scale epidemiologic studies and clinical trials. (iv) Research over the last 6 years on novel modalities for the treatment of HIV‐OLs has been reported for OC and OHL.